Kulturfolk, barbarer och gulaschbaroner En studie av svenska läroverkselevers syn på första världskriget 1913-1917 - Johansson, Roger (2017)
The purpose of this essay is to examine the student examination essays of Swedish student at the Läroverk from 1913-1917 in order to find out the opinions of the students regarding world war I and its impact on Sweden, with particular focus on the opinion of the warring parties and on the ideals that the students hail as good or bad. Through a qualitative, hermeneutic method 60 essays by students from Karlstad and Luleå are examined. Theoretically this essay bases its opinions on the findings of Pontus Rudberg and Martin Skoog regarding causes of the war and war-guilt and on the findings of Lina Sturfelt regarding the opinions of the war as such and its impact on Sweden. The result of this essay is that the students had a strong focus or war reasons rather than war guilt, which is somewhat contradicting the findings of Rudberg and Skoog. Regarding the reasons their opinions are well in line with the findings of Rudberg and Skoog. The students paint a complex picture with several different reasons behind the world war I. Among those reasons are egoism, power struggle between nations, mainly Germany and the United Kingdom and French revanchism after the Franco German war of 1870-1871. Concerning the loyalties of the students the essay show that they possibly leaned towards Germany but that the evidence for that is pretty scarce. The most obvious trait in this respect is instead mistrust and derogatory remarks towards Russia. The students go as far as portraying Russians as barbarians, while the French are a people of culture. Regarding the Swedish neutrality, the opinion of the students is unanimous. They stood up for neutrality and wanted no part in the war. They align themselves with Lina Sturfelt’s positive but “Small Swedish” view of neutrality. When it comes to impact on Sweden the students see two different kinds of impact: economic and political. Ideals such as empathy, consensus and trust in authorities are brought forward by the students, while they are also deeply negative towards the so called goulash ...